Water balance and its variability in El Niño and La Niña periods aiming at erosive oscillations in Amparo de São Francisco - Sergipe – Brazil (Research, Society and Development, 2020)
The objective is to estimate the normal climatological water balance in phase of the El Niño phenomena (a), aiming at the occurrence of erosive variability for the municipality of Amparo de São Francisco - SE, providing information to government decision makers so that they can carry out planning aimed at contain soil losses in the region. We used the data of average monthly and annual precipitation and the values ​​of the average air temperature estimated by the Estima_T software for the period 1963-2019. To determine the soil erosivity factor, the equation proposed by Wischmeier was used for the same period of precipitation and thermal indices. Erosive forms today, both by water and wind, are responsible for around 56% and 28% of soil degradation in the world. The erosion problems in the study area are the result of the combination of a fast process of occupation and techniques of the territory, fragile soils and a climate regime conducive to its intense occurrence. Since these processes are not just physical forms. The aridity indices have a greater contribution to the erosion process was recorded in the period of occurrence of La Niña (3.63%), followed by the periods of El Niño (21.78%) and the rainfall series (1963-2019) (35 , 85%). The water indexes presented the following variability for the period of the series (-12.37%), El Niño (10.96%) and La Niña (71.06%). The humidity indexes fluctuated with 8.76% in the series, 24.02% in El Niño and 73.23% in La Niña. It is known that the lower the Ia, the greater the occurrence of erosion.